Power Flow Control in Transmission Line Using IPFC Equipped with Fuzzy Logic Controller (International Journal of Engineering and Computer Science, 2015)
The interline power flow controller (IPFC) is a Flexible ac transmission based device comprises voltage source converter for the series compensation in multiline transmission systems. The IPFC is capable to manage power between two or more interconnected lines. The voltage source converter injects reactive power which is used to flow the active power in the transmission lines. Flow of electrical energy in the transmission line can be controlled adequately by utilizing IPFC. This paper proposed the compensation in the transmission line using IPFC for managing power flow and comprehensive analysis of active power is presented with and without IPFC using projected circuit models. The matlab/simulink tools equipped with fuzzy logic controller is using for simulation.